2003
DOI: 10.1080/1354750031000090660
|View full text |Cite
|
Sign up to set email alerts
|

Development, validation and characterization of an analytical method for the quantification of hydrolysable urinary metabolites and plasma protein adducts of 2,4- and 2,6-toluene diisocyanate, 1,5-naphthalene diisocyanate and 4,4'-methylenediphenyl diisocyanate

Abstract: Occupational exposure to diisocyanates within the plastic industry causes irritation and disorders in the airway. The aim of this study was to develop, validate and characterize a method for the determination of 2,4-toluenediamine (2,4-TDA), 2,6-toluenediamine (2,6-TDA), 1,5-diaminonaphthalene (1,5-NDA) and 4,4'-methylenedianiline (4,4'-MDA) in hydrolysed urine and plasma, and to study the correlation between the plasma and urinary levels of these potential biomarkers of 2,4-toluene diisocyanate (2,4-TDI), 2,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 8 publications
1
42
1
Order By: Relevance
“…The biomarker levels in the urinary and plasma samples were analyzed according to Sennbro et al (2003). In principle, the biological samples were hydrolyzed for 24 h in 0.3 M NaOH in order to release the diisocyanate-related diamines 2,4-toluene diamine (TDA), 2,6-TDA, methylene dianiline (MDA) and naphthalene diamine (NDA).…”
Section: Analysis Of Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…The biomarker levels in the urinary and plasma samples were analyzed according to Sennbro et al (2003). In principle, the biological samples were hydrolyzed for 24 h in 0.3 M NaOH in order to release the diisocyanate-related diamines 2,4-toluene diamine (TDA), 2,6-TDA, methylene dianiline (MDA) and naphthalene diamine (NDA).…”
Section: Analysis Of Biomarkersmentioning
confidence: 99%
“…When diisocyanates are inhaled they react with biomolecules (Sennbro et al 2003). In the blood it has been shown that the diisocyanates are mainly bound to serum albumin (Lind et al 1997a;Johannesson et al 2004) and the half-life of the adducts in plasma has been reported to be 21 days which is similar to that of albumin (Lind et al 1997b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbed NDI and MDI form protein adducts in blood , Sennbro et al 2003, preferentially with serum albumin in plasma (Johannesson et al 2004). MDI metabolites are excreted in urine as low-molecular weight conjugates (Lind et al 1996a).…”
Section: Introductionmentioning
confidence: 99%
“…By hydrolysis of biological samples from exposed subjects, the NDI-and MDI-related metabolites are released as 1,5-naphthalenediamine (NDA) and 4,4'-methylenedianiline (MDA), respectively. Methods for the quantification of MDA in hydrolysed biological fluids have been described (Brunmark et al 1992, Schütze et al 1995, Dalene et al 1997, Kääriä et al 2001, Sennbro et al 2003, but few studies have concerned biological monitoring of exposure to MDI (Skarping et al 1996, Kääriä et al 2001. For NDA, one method for determination in hydrolysed urine and plasma has been described (Sennbro et al 2003), and no studies on biological monitoring of NDI have been reported.…”
Section: Introductionmentioning
confidence: 99%